Role Play as Pedagogical Tool to Enhance Speaking Skills: Students’ and Lecturer’s Perception - Widyani, Annisa Fitri; Ngafif, Abdul; Basuki, Basuki (Scripta : English Department Journal, 2025)
The research aims to explore the students’ perception and to know the lecturer’s perception of role play as a pedagogical tool to enhance English speaking skills. Then, it explores the perceptions of the third-semester students and a Public Speaking course lecturer as its respondents. The use of role-play as a pedagogical tool to enhance English speaking skills in the Public Speaking course at Universitas Muhammadiyah Purworejo is the main topic of this research. Employing a qualitative descriptive design, data were collected through questionnaires and in-depth interviews involving 50 students and one lecturer. The results revealed that both students and the lecturer viewed role play positively, highlighting its effectiveness in improving speaking fluency, boosting confidence, and increasing engagement. Role play provided realistic and interactive contexts for students to apply language skills while reducing anxiety and promoting active participation. However, challenges such as nervousness and lack of preparation were noted, indicating the need for supportive learning environments. These findings suggest that role play should be integrated more frequently into speaking classes to foster communicative competence and real-life speaking readiness.